A growing burden: the pathogenesis, investigation and management of non-alcoholic fatty liver disease. Issue 12 (4th May 2007) - Riley, P; O'Donohue, J; Crook, M
Abstract : Non-alcoholic fatty liver disease (NAFLD) is the most common hepatic disorder in western countries, and its incidence is increasing. This review outlines the significant health burden posed by NAFLD and discusses what is presently known about its pathogenesis, including the roles of the metabolic syndrome, obesity, insulin resistance, hepatic steatosis, reactive oxygen species, inflammatory cytokines and adipocytokines. The way in which NAFLD is clinically diagnosed is described, and areas of uncertainty surrounding its investigation are identified, before discussing the relative merits of the limited treatment options available and looking ahead to potential therapeutic strategies for the future.